The relationship between followers' typology, conformity and organizational citizenship behavior / Azlyn Ahmad Zawawi … [et al.] - Zawawi, Azlyn Ahmad; Kamarunzaman, Nur Zafifa; Hussin, Zaliha; Campbell, James (Research Management Institute (RMI), 2013)
The compositions of followers and the intensity of citizenship behavior in teams have been a research interest of behavioral psychology. Team theory suggested interesting points to begin with; members of a team often think alike in an insight called 'mental model'. This mental model allows flow of communication and smooth continuation of task implementation. The fact is that, this mental model guides most members to think in a similar way and it is an advantage to task success. In order to have a good structure of mental model, teams have to understand each other's behavior, and so does the leaders. This may include understanding the type of followers that they are. Followership is a factor that drives organizational effectiveness. This research entails the relationships between followers' typology, conformity and organizational citizenship behavior. It involved 271 military men from two infantry units in Kedah, Malaysia. Data was collected at individual basis to project their followers' typology, conformity and OCB. Results indicated strong positive relationships between all hypothesized variables.